TONE MAPPING METHOD AND IMAGE PROCESSING algorithms under BRIght ambient lightING - A. V. Sycev; A. A. Stepanov; A. G. Smirnov; K. .. Blankenbach (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The algorithms for image enhancement under bright ambient light condition on the display surface, which optimizes the viewing experience on mobile and automotive displays, were developed. The tone mapping algorithms D L / L and D E with color rendering take into account not only the intensity of ambient illuminance, but also the parameters of the display itself. Display options are quite easy to integrate into the algorithm. This publication shows detailed work of algorithms, as well as provides results of applying algorithms on an image.